If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6 = 6(x + 2) + 8 Reorder the terms: -6 + 4x = 6(x + 2) + 8 Reorder the terms: -6 + 4x = 6(2 + x) + 8 -6 + 4x = (2 * 6 + x * 6) + 8 -6 + 4x = (12 + 6x) + 8 Reorder the terms: -6 + 4x = 12 + 8 + 6x Combine like terms: 12 + 8 = 20 -6 + 4x = 20 + 6x Solving -6 + 4x = 20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 4x + -6x = 20 + 6x + -6x Combine like terms: 4x + -6x = -2x -6 + -2x = 20 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + -2x = 20 + 0 -6 + -2x = 20 Add '6' to each side of the equation. -6 + 6 + -2x = 20 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 20 + 6 -2x = 20 + 6 Combine like terms: 20 + 6 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| 9x-4=2x-3 | | 8b+6(-6-2b)=4+b | | x-5+x-5+x-5+x-5=12+x+x | | 2x-3=2(x+4) | | 18(w+3)-45=18+54 | | 25-7a=28+4a | | 5x^4-30x^2= | | 32=5-4a-5a | | 0.02(y-9)+0.20y=0.16y-0.6 | | 2(9s+7)-10s=2(4s+2)-8 | | 18-2x=-36 | | 5w-6+3w=-12 | | -4-3x=17 | | 4+3-939340823094+6-x=-34 | | (5x^2y-2xy^2+3xy-5)(-2x^2y-3xy^2+4xy+7)= | | -4(3x-2)=2x+17 | | 4x/20+10=2x-26 | | 6x+4y=-24 | | 2y-8=6y | | 9x-4=x-3 | | 2+6x+5x=-130 | | 4(x-2)=4(x-3) | | 6t+20=9t+20 | | -58-4x=17+x | | 0.50x+0.45(30)=36.5 | | (3+x)2=x+2 | | 15y-6-10y=9 | | 25(10-x)=25x+250 | | 2y+-4y+y=40 | | 1.5t^2+12t-52=0 | | 7-4(5+x)=3x-7(2x-1) | | 24-2s=2-(2s-3) |